Why do Emerging Market Firms Engage in Voluntary Environmental Management Practices? A Strategic Choice Perspective. (19th March 2019) - Tatoglu, Ekrem; Frynas, Jedrzej George; Bayraktar, Erkan; Demirbag, Mehmet; Sahadev, Sunil; Doh, Jonathan; Koh, S. C. Lenny
Abstract: In this paper, we investigate firms' decisions to engage in voluntary environmental management (VEM) practices within an emerging market context. Drawing on the strategic choice and the resource‐based view perspectives, we report results from a survey of VEM practices – a specific form of self‐governance – drawing on a sample of 519 Turkish firms from various industries to identify important strategic antecedents of firms' decisions to engage in such practices. We find that as firms become more customer focused, more inclined to pursue a differentiation strategy and subject to a higher level of strategy‐oriented stakeholder focus, they tend to implement higher levels of VEM practices, with important implications for research, policy and practice for both emerging and developed markets.